2001
DOI: 10.1021/ja010202a
|View full text |Cite
|
Sign up to set email alerts
|

Stable Colloidal Dispersions of Fullerenes in Polar Organic Solvents

Abstract: Colloidal dispersions of C60 and C70 were prepared by simply mixing a fullerene solution in a good solvent with a poor polar organic solvent for fullerenes. The process was very easy and fast and the formation of particles with average diameter in the colloidal range was detected immediately after the components were mixed. The formation and the properties of the fullerene particles were studied mainly with dynamic light scattering and high-resolution transmission electron microscopy. The most interesting find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
198
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(214 citation statements)
references
References 46 publications
(111 reference statements)
12
198
1
1
Order By: Relevance
“…5,11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In highly polar organic solvents, the molecular solubility of fullerenes is negligible, 14,15 but they readily form colloidal solutions. [9][10][11][12][13][14][31][32][33][34][35] The state of fullerenes, either molecular or colloidal, in the so-called 'good' or 'strong' solvents, such as CS 2 , toluene, and benzene, is still a matter of discussion. 8,10,11,14,[36][37][38][39][40] Some authors believe that in such a case, aggregates appear only as a result of sonication.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In highly polar organic solvents, the molecular solubility of fullerenes is negligible, 14,15 but they readily form colloidal solutions. [9][10][11][12][13][14][31][32][33][34][35] The state of fullerenes, either molecular or colloidal, in the so-called 'good' or 'strong' solvents, such as CS 2 , toluene, and benzene, is still a matter of discussion. 8,10,11,14,[36][37][38][39][40] Some authors believe that in such a case, aggregates appear only as a result of sonication.…”
Section: Introductionmentioning
confidence: 99%
“…8,38,41 In contrast, in polar or 'poor' organic solvents, the formation of colloidal species is undoubtedly proven. 9,[11][12][13][14][31][32][33][34][35] Typical examples are aggregates in N-methylpyrrolidin-2-one-acetonitrile mixed solvent, 3 toluene (benzene) mixtures with acetonitrile, 9,12,36 N-methylpyrrolidin-2-one 11,33 and other polar solvents, 13 DMSO, 31 acetonitrile, acetone, ethanol, methanol, and other polar solvents. 32,35,42 Though the stability and coagulation of aqueous C 60 colloids via electrolytes has been examined in full, 14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][43][44][45][46][47][48][49] the corresponding research for organosols is absent to the best of the authors knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Alargova et al, 2001) Solvents, distinctly dissolving one component of the blend, induce the aggregation of nanofibers and nanoparticles in the solvent prior to film deposition. (Yao et al, 2008) It was shown that (independent of the concentration of the additive) fullerene molecules crystallized into distributed aggregates in the presence of a "bad" solvent in the host solvent.…”
Section: Processing Additivesmentioning
confidence: 99%
“…9) it was shown that the PCE improves almost by a factor of two. (Alargova et al, 2001;Peet et al, 2007) Fig. 10.…”
Section: Processing Additivesmentioning
confidence: 99%